“Sometimes it is difficult for us to stand up and change this”: an analysis of power within priority-setting for health following devolution in Kenya - Rosalind McCollum; Miriam Taegtmeyer; Lilian Otiso; Nelly Muturi; Edwine Barasa; Sassy Molyneux; Tim Martineau; Sally Theobald (BMC Health Services Research, 2018)
Abstract Background Practices of power lie at the heart of policy processes. In both devolution and priority-setting, actors seek to exert power through influence and control over material, human, intellectual and financial resources. Priority-setting arises as a consequence of the needs and demand exceeding the resources available, requiring some means of choosing between competing demands. This paper examines the use of power within priority-setting processes for healthcare resources at sub-national level, following devolution in Kenya. Methods We interviewed 14 national level key informants and 255 purposively selected respondents from across the health system in ten counties. These qualitative data were supplemented by 14 focus group discussions (FGD) involving 146 community members in two counties. We conducted a power analysis using Gaventa’s power cube and Veneklasen’s expressions of power to interpret our findings. Results We found Kenya’s transition towards devolution is transforming the former centralised balance of power, leading to greater ability for influence at the county level, reduced power at national and sub-county (district) levels, and limited change at community level. Within these changing power structures, politicians are felt to play a greater role in priority-setting for health. The interfaces and tensions between politicians, health service providers and the community has at times been felt to undermine health related technical priorities. Underlying social structures and discriminatory practices generally continue unchanged, leading to the continued exclusion of the most vulnerable from priority-setting processes. Conclusions Power analysis of priority-setting at county level after devolution in Kenya highlights the need for stronger institutional structures, processes and norms to reduce the power imbalances between decision-making actors and to enable community participation.